Analysis Of Current Account And Deposit Savings On The Total Sources Of Public Funds At Indonesian Sharia Banks - Ade Yoelisa; Alia Sari; Putri Nuraini (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the role of demand deposits and time deposits in total public funding sources at Bank Syariah Indonesia. Sharia banks function as intermediary institutions that collect public funds through sharia-compliant savings products, particularly demand deposits and time deposits. This research employs a qualitative approach using a literature review method, utilizing secondary data obtained from Bank Syariah Indonesia’s annual reports, scientific journals, Islamic banking literature, and official publications from the Financial Services Authority. Data analysis was conducted using descriptive qualitative techniques by comparing the findings of previous studies related to the contribution of each product to fund mobilization. The results indicate that time deposits possess relatively stable and fixed-term characteristics, thereby supporting medium- and long-term financing, although their contribution to fluctuations in total public funding is not always immediate. In contrast, demand deposits are more liquid and closely associated with customers’ transactional activities, enabling them to contribute more actively to the formation of total public funding sources. This study concludes that balanced and integrated management of demand deposits and time deposits is essential to optimize public fund collection and to maintain the stability and performance of Islamic banking in Indonesia. Keywords: Islamic Banks in Indonesia, Demand Deposits, Time Deposits, Third-Party Funds, Public Funding Sources AbstrakPenelitian ini bertujuan untuk menganalisis peran giro dan deposito dalam total sumber dana masyarakat pada Bank Syariah Indonesia. Bank syariah berfungsi sebagai lembaga intermediasi yang menghimpun dana masyarakat melalui produk simpanan berbasis syariah, khususnya giro dan deposito. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan studi kepustakaan, yang memanfaatkan data sekunder berupa laporan tahunan Bank Syariah Indonesia, jurnal ilmiah, literatur perbankan syariah, serta publikasi resmi Otoritas Jasa Keuangan. Analisis data dilakukan dengan teknik deskriptif kualitatif melalui perbandingan hasil penelitian terdahulu terkait kontribusi masing-masing produk dalam penghimpunan dana. Hasil penelitian menunjukkan bahwa deposito memiliki karakteristik yang relatif stabil dan berjangka waktu tertentu, sehingga berperan dalam mendukung pembiayaan jangka menengah dan panjang, meskipun kontribusinya terhadap perubahan total sumber dana masyarakat tidak selalu bersifat langsung. Sementara itu, giro bersifat likuid dan sangat berkaitan dengan aktivitas transaksi nasabah, sehingga berkontribusi lebih aktif dalam pembentukan total sumber dana masyarakat. Penelitian ini menyimpulkan bahwa pengelolaan giro dan deposito yang seimbang dan terintegrasi diperlukan untuk mengoptimalkan penghimpunan dana masyarakat serta menjaga stabilitas dan kinerja perbankan syariah di Indonesia. Kata kunci: Bank Syariah Indonesia, Giro, Deposito, Dana Pihak Ketiga, Sumber Dana Masyarakat